Footwear affects the gearing at the ankle and knee joints during running - Braunstein, B.; Arampatzis, A.; Eysel, P.; Brüggemann, G. P. (Journal of Biomechanics, 2010)
The objective of the study was to investigate the adjustment of running mechanics by wearing five different types of running shoes on tartan compared to barefoot running on grass focusing on the gearing at the ankle and knee joints. The gear ratio, defined as the ratio of the moment arm of the ground reaction force (GRF) to the moment arm of the counteracting muscle tendon unit, is considered to be an indicator of joint loading and mechanical efficiency. Lower extremity kinematics and kinetics of 14 healthy volunteers were quantified three dimensionally and compared between running in shoes on tartan and barefoot on grass. Results showed no differences for the gear ratios and resultant joint moments for the ankle and knee joints across the five different shoes, but showed that wearing running shoes affects the gearing at the ankle and knee joints due to changes in the moment arm of the GRF. During barefoot running the ankle joint showed a higher gear ratio in early stance and a lower ratio in the late stance, while the gear ratio at the knee joint was lower during midstance compared to shod running. Because the moment arms of the counteracting muscle tendon units did not change, the determinants of the gear ratios were the moment arms of the GRF's. The results imply higher mechanical stress in shod running for the knee joint structures during midstance but also indicate an improved mechanical advantage in force generation for the ankle extensors during the push-off phase.